177Lu-/68Ga-PSMA Theranostics in Recurrent Glioblastoma Multiforme: Proof of Concept. (December 2020) - Kumar, Arunav; Ballal, Sanjana; Yadav, Madhav Prasad; ArunRaj, S.T.; Haresh, K.P.; Gupta, Subhash; Damle, Nishikant Avinash; Garg, Ajay; Tripathi, Madhavi; Bal, Chandrasekhar
Abstract : Abstract: A 37-year-old man, treated case of left temporal glioblastoma presented with headache, seizures, and progressive right-sided weakness with MRI evidence of recurrence. Exploratory 68 Ga-PSMA PET/CT demonstrated PSMA expression in the recurrent lesion; it was decided to treat this patient with 177 Lu-PSMA-617. After 3 cycles of 177 Lu-PSMA-617, 68 Ga-PSMA PET/CT showed significant reduction in PSMA uptake and regression in size of lesion on MRI with improvement in patient's symptoms and performance status. 177 Lu-/ 68 Ga-PSMA theranostics has potential in patients with recurrent glioblastoma multiforme when other therapeutic options are not feasible.